LEGAL AND ECONOMIC PRINCIPLES OF THE FOREIGN POLICY OF INDEPENDENT AZERBAIJAN IN RELATION TO NEIGHBORING COUNTRIES - Katana Gafarova (Baltic Journal of Economic Studies)
The subject of the study is the conceptual, theoretical, empirical, methodological and applied foundations of the legal and economic principles of the foreign policy of independent Azerbaijan in relation to neighbouring countries. Methodology. General scientific and special legal methods were used in the process of research. The analysis determined the quantitative characteristics of the economic and legal principles of the foreign policy of independent Azerbaijan in relation to the neighbouring countries as a social phenomenon. The synthesis provided the formation of common features of the legal and economic principles of the foreign policy of independent Azerbaijan in relation to the neighbouring countries. The comparative legal method allowed to identify the characteristic similarities and differences in the international regulatory legal acts, national legislation in this sphere, as well as the prospects for improvement of legal regulation of such relations. The formal-legal method created the conditions for the formulation of conclusions on the effectiveness of measures defined by the international and national legislation in the field of construction of economic and legal principles of foreign policy of independent Azerbaijan in relation to the neighbouring countries. The purpose of the article is to define the economic and legal foundations of the independent Azerbaijan's foreign policy towards neighbouring countries. The results of the study showed that the economic and legal principles of independent Azerbaijan's foreign policy towards neighbouring countries are based on respect for territorial integrity, independence, national identity, free economic development, ensuring security and creating an image of a safe and reliable partner both within the Southern Transcaucasus region and beyond. Conclusion. The relationship between the economic and legal components in the content of the country's foreign policy activity is differentiated, where the economy acts as a means and functionality for the use of a certain set of resources for the production, sale, distribution and consumption of public goods, and the law ensures the structuring of all social phenomena according to certain rules of behaviour in terms of satisfying public and private interests in the context of building a compromise model of the relationship between them. The economic principles that underpin Azerbaijan's relations with neighbouring countries are predicated on geographical and geopolitical factors, which exert an indirect influence on relations in the oil and gas industry, the construction of transport routes and ways of moving goods, and the ensuring of the region's energy security and other geopolitical formations. In this context, the potential for the implementation of projects to create free economic zones is noted. In the economic sphere, Azerbaijan chooses the means and instruments of co-operation that correspond to the foundations of a civilised, market-based approach to the comprehensive solution of security, resource, energy and financial problems. Azerbaijan is involved in the implementation of many projects of security, energy and logistic nature, including "One Belt, One Road", "Belt and Road", "Middle Corridor", "North-South", "Crossroads of the World", etc. Among the countries occupying a dominant position in the world economy, Azerbaijan has developed the deepest and broadest relations with China, which is reflected in the relevant foreign economic projects. The legal basis of Azerbaijan's co-operation with neighbouring countries is determined on three levels: 1) universal international law; 2) regional international law; 3) national. The dispositive principles of co-operation with the EU are described in detail, with particular reference to the peculiarities of the legal regime established by the founding documents of this organisation and the fundamental founding agreements. Attention is drawn to the rather defining provisions of the intergovernmental agreements of Azerbaijan with China and Kazakhstan, in view of a number of common interests in the field of security, energy independence, logistics and other areas of the economy. The potential for the advancement of such relations is acknowledged, with the premise of exponential diversification being established as a foundation. This diversification is characterised by the acceleration of the non-oil sector, irrespective of the magnitude of oil revenues, and the integration of information and communication technologies across various societal domains.